Peningkatan Kinerja Siakad Menggunakan Metode Load Balancing dan Fault Tolerance Di Jaringan Kampus Universitas Halu Oleo - Alimuddin Alimuddin; Ahmad Ashari (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
The application of academic information system (siakad) a web-based college is essential to improve the academic services. Siakad the application has many obstacles, especially in dealing with a high amount of access that caused the overload. Moreover in case of hardware or software failure caused siakad inaccessible. The solution of this problem is the use of many existing servers where the load is distributed in the respective server. Need a method of distributing the load evenly in the respective server load balancing is the method by round robin algorithm so high siakad scalability. As for dealing with the failure of a server need fault tolerance for the availability siakad be high. This research is to develop methods of load balancing and fault tolerance using software linux virtual server and some additional programs such as ipvsadm and heartbeat that has the ability to increase scalability and availability siakad. The results showed that with load balancing to minimize the response time to 5,7%, increase throughput by 37% or 1,6 times and maximize resource utilization or utilization of 1,6 times increased, and avoid overload. While high availability is obtained from the server's ability to perform failover or move another server in the event of failure. Thus implementing load balancing and fault tolerance can improve the service performance of siakad and avoid mistakes.